Pengaruh Ketebalan Lapisan Dentin Terhadap Kekuatan Tarik Pada Gigi Tiruan Cekat Keramik - Logam. - Riska Handayani (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Metal ceramic fixed denture is a combination of ceramic and metal which aims to obtain good mechanical properties from metal coping and good aesthetic properties of ceramics. The metal coping and the ceramic coating is bonded due to chemical bonds and mechanical bonds. The purpose of this study was to determine the effect of the thickness of the dentine layer on the tensile strength of metal-ceramic fixed dentures with a dentin layer thickness of 0.5 mm, 0.6 mm, 0.7 mm. The research used laboratory experimental in vitro, with a post-test only control group design by measuring and observing after treatment. The total number of samples contained 27 metal ceramics, grouped into 3 parts, namely: 9 samples with a dentin layer thickness of 0.5 mm, 9 samples with a dentin layer thickness of 0.6 mm, and 9 samples with a layer thickness of 0.7 mm. There is an effect of the thickness of the dentin layer on the tensile strength of metal-ceramic fixed dentures with a metal base material of Co-Cr (p = 0.000). The thickness of the dentine layer was 0.7 mm which resulted in the most optimal tensile strength when compared to the thickness of the dentine layer of 0.5 mm and 0.6 mm for metal-ceramic fixed dentures with the base material of Co-Cr gallon.